Assessment and Management of Occupational and Health Risks Associated with the Shipbuilding Industry in Bangladesh - Review (MIST International Journal of Science and Technology, 2025)
Bangladesh’s shipbuilding sector plays a significant contribution to the country’s economy. However, it is also associated with occupational risks for its workforce. This paper aims to review and explore existing literature on assessing and managing these risks within the context of the Bangladeshi shipbuilding industry. The review delved into different types of hazards encountered by shipyard workers, including physical, chemical, and biological dangers, by analyzing incident reports, safety audits, and exposure data elaborated in the literature. Furthermore, the review also examines established methods applied to the international and local shipbuilding industry for risk assessment and management and makes a comparison to find the gap in the literature. It is revealed from the study that a significant number of the literature containing a diverse range of focus areas within the shipbuilding sector is found worldwide, but only 20% of them is found relevant to the Bangladeshi shipbuilding industry and among them, only very few papers deal with Occupation Health and Safety assessment technique. This highlights a huge gap in the literature and suggests a need for more studies in terms of Occupational Health and Safety management in the context of Bangladesh shipbuilding.MIJST, Vol. 12, December 2024 : 29-38DOI: https://doi.org/10.47981/j.mijst.12(02)2024.483(29-38)